Nuda vida y goce. // Bare life and jouissance. - Laura Arias. (Affectio Societatis, 2010)
From the point of view that connects politics and psychoanalysis, the aim of this essay is to investigate the causes of the annihilation of the subject in the totalitarian regimes, making him a victim of power, reduced to a bare life. This question leads us to analyze the jouissance within the frame of a regime that proposes the unification of a universal jouissance. These questions are considered to be relevant in the field that makes possible the intersection between politics and subjectivity. The direct proposal of this essay is related to thought, by trying to bring thought into play, in conjunction with the concepts of jouissance and the annihilation of the subject in the totalitarian regimes. It deals with the articulation between thought and jouissance and uses these ideas like conceptual tools, with the aim of considering the subjectivity of the time. // Desde el punto de vista que relaciona la política con el psicoanálisis, la propuesta de este ensayo trata de interrogar qué produce la aniquilación del sujeto en los regímenes totalitarios, al convertirlo en víctimas del poder, reducido a nuda vida. Este cuestionamiento nos conduce a preguntarnos sobre el goce en el marco de un régimen que propone la unificación de un goce universal. Consideramos pertinentes estos cuestionamientos en la vertiente que posibilita el cruce entre política y subjetividad. La propuesta expresa de este ensayo se relaciona con el pensar; con la posibilidad de recuperar una reflexión sobre el pensar, tratando de ponerlo en escena, en conjunción con el goce y la aniquilación del sujeto en los regímenes totalitarios. Se trata de una articulación entre pensar y goce y toma estas nociones como herramientas conceptuales, en el interés por considerar la subjetividad de la época.